2013
DOI: 10.1155/2013/694941
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Myofascial Trigger Point Dry Needling in the Prevention of Pain after Total Knee Arthroplasty: A Randomized, Double-Blinded, Placebo-Controlled Trial

Abstract: The aim of this study was to determine whether the dry needling of myofascial trigger points (MTrPs) is superior to placebo in the prevention of pain after total knee arthroplasty. Forty subjects were randomised to a true dry needling group (T) or to a sham group (S). All were examined for MTrPs by an experienced physical therapist 4–5 hours before surgery. Immediately following anesthesiology and before surgery started, subjects in the T group were dry needled in all previously diagnosed MTrPs, while the S gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
95
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(100 citation statements)
references
References 36 publications
5
95
0
Order By: Relevance
“…The result of the present study was consistent with the results derived from the research by Orlando Mayoral and colleagues in 2013 on patients with knee arthroplasty [29]. In 2007, Sierre Adam and colleagues did their research on two treatment groups (Chiropractic-Chiropractic and DN) in patients with patellofemoral pain syndrome.…”
Section: Assessment Of Painsupporting
confidence: 90%
See 1 more Smart Citation
“…The result of the present study was consistent with the results derived from the research by Orlando Mayoral and colleagues in 2013 on patients with knee arthroplasty [29]. In 2007, Sierre Adam and colleagues did their research on two treatment groups (Chiropractic-Chiropractic and DN) in patients with patellofemoral pain syndrome.…”
Section: Assessment Of Painsupporting
confidence: 90%
“…Orlando Mayoral and colleagues in 2013 applied the DN technique in patients with knee arthroplasty. They found that the maximum of isometric muscle strength in the intervention group was similar to placebo group after treatment [29]. In 2009, Adam Sayers investigated the effect of DN on the vastus medialis muscle in patients with patella femoral pain syndrome.…”
Section: Assessment Of Quadriceps Muscle Strengthmentioning
confidence: 99%
“…After the full review process, 12 studies were selected for inclusion. 2,7,12,24,27,28,32,33,35,36,38,43 After contact with primary authors of included studies, 1 further study was identified for inclusion, 6 resulting in a total of 13 studies. The absolute degree of rater agreement for the first and second stages of the study selection was 86% and 93%, respectively.…”
Section: Study Selectionmentioning
confidence: 99%
“…This systematic review focused on musculoskeletal pain and included 13 studies: 6 on neck pain (5 on mechanical neck pain 6,24,28,32,43 and 1 on chronic whiplash-associated disorder 38 ), 1 on postoperative shoulder pain, 2 1 on chronic lower back pain, 33 1 on total knee arthroplasty, 27 1 on chronic ankle instability, 35 2 on myofascial pain, 12,36 and 1 on fibromyalgia. 7 Inclusion and exclusion criteria varied greatly across the studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…22 Similarly, a recent review concluded that TrP DN was effective for lower-quarter pain syndromes in the short term; however, its effects on function have been questioned. 29 Some studies included in this review support the use of TrP DN of the knee musculature for knee osteoarthritis 19 or after knee replacement 28 ; however, no study has previously investigated the effect of TrP DN in patients with PFP. Therefore, the objective of this study was to compare the effects of adding TrP DN to a manual therapy and exercise program on pain, function, and disability in people with PFP.…”
Section: Participantsmentioning
confidence: 96%